Experimental and Numerical Investigation of Different Types of Jacketing Effect on Retrofitting RC Short Columns Using ECC Concrete - Dadmand, Behrooz; Pourbaba, Masoud; Riahi, Ramin (Periodica Polytechnica Civil Engineering, 2022)
Given the deterioration of civil infrastructure throughout the world, developing more efficient repair and strengthening is essential. Jacketing is one of the most common methods for retrofitting reinforced concrete (RC) columns. Notably, using engineered cementitious composite (ECC) within the jacketing area increases the bearing capacity and significantly enhances the ductility of the columns. The recent development of ECC concrete with suitable compressive strength and higher ductility of about 5 % can significantly enhance the performance of reinforced concrete structures. The behavior of retrofitted RC columns depends heavily on the cohesion between the jacket and the original column as well as the mechanical properties of the jacketing materials. This study investigates jacketed square and circular RC columns using ECC and conventional/normal concrete (NC) using different casing techniques to retrofit RC columns, namely galvanized mesh, U and L-shape joints, removing the cover, core drilling, and integrated models. All specimens were subjected to a compression test. The results indicate that in both square and circular specimens, the use of ECC as a super ductile material and vertical U-shaped elements to connect the longitudinal rebars of the casing and the core leads to much higher ductility and bearing capacity than in NC specimens. These elements also showed suitable ductility because of using ECC as a super ductile material. In order to optimize these methods, finite element analysis (FEA) was conducted using Abaqus software to verify experimental models, as well as a parametric study to achieve an optimum design of the jacketing.